Transcriptom Analysis of Auricularia auriculla-judae Fruit Body Treated with Gamma Radiation on Mycelium - Jeong-Heon Kim; Youn-Jin Park; Myoung-Jun Jang (Mycobiology, 2025)
Fungi have a high resistance to gamma radiation. Previous studies elucidating the resistance mechanisms to gamma radiation have mainly been conducted using yeast model organisms, but molecular-level mechanisms targeting fungi have been largely unexplored. In order to examine the response of A. auricula-judae to gamma radiation, we conducted comparative transcriptome analysis using RNA-Seq on fruit bodies derived from mycelium exposed with 200 Gray of gamma radiation. A total of 69,183 unigenes were generated, and annotation was performed through two libraries. According to GO analysis, catalytic activity, cell part, and cellular process groups were identified as the major groups responding to gamma radiation. Differentially expressed genes revealed inhibited expression in amino acid metabolism, carbohydrate metabolism, and cell cycle regulation genes. Furthermore, enhanced cell death promoted resistance by eliminating unstable cells. DNA repair genes were up-regulated, indicating a common defense mechanism of fungi that increases genome integrity by repairing DNA damaged by gamma radiation. Conversely, genes related to antioxidants and laccase were down-regulated, suggesting that resistance response through resolving oxidative stress induced by gamma radiation did not occur. Our study provides valuable data for understanding not only the response of A. auricula-judae to gamma radiation but also the resistance responses of edible mushrooms to gamma radiation.